Light-induced rearrangement from macrocyclic to bicyclic lactam: A case study of N-chlorinated laurolactam - Zubčić Gabrijel; Pavić Kristina; You Jiangyang; Vrček Valerije; Portada Tomislav; Bešić Erim; Šakić Davor (Acta Pharmaceutica, 2024)
Converting macrocycle lactams into bicyclic lactams is proposed as an additional way to further increase the metabolic stability of peptide-based drugs. Unfortunately, the synthesis of bicyclic lactams has to start almost from scratch. This study explores the Hofmann-Löffler-Freytag (HLF) reaction mechanism and products as a potential late-stage functionalisation strategy for facile conversion of macrocyclic to bicyclic ring. Laurolactam, a macrocyclic amide, exhibits significant potential for transformation into bioactive bicyclic structures with smaller, β-, γ-, δ-, and ε-lactam rings, further increasing rigidity and hydrolytic stability. With irradiation provided by a 370 nm lamp, light-induced rearrangement reaction was monitored using nuclear magnetic resonance (NMR), while involved radical intermediates were trapped using N-tert-butyl-α-phenylnitrone (PBN) spin-trap and characterised via EPR. While only two radical adduct types were identified in the electron para magnetic resonance (EPR) (C-centered radical and chlorine radical), all eight possible products are observed in the NMR. Quantum chemical calculations provide deeper insights into reaction thermodynamics and kinetics, explaining why the N-centered radical was not observed. This research highlights the feasibility of using the HLF reaction to transform macrocyclic lactams into stable bicyclic drug candidates, paving the way for new therapeutic developments.